Study of the Academic Course ‘Management’: Its Need, Scope and Significance in Modern Period - Karki, Nabaraj (BARUN Journal, 2024)
The academic course of ‘Management’ is a multidisciplinary field of study that focuses on the principles and practices of effectively leading and coordinating resources within organizations to achieve specific goals and objectives. It encompasses a wide range of topics related to planning, organizing, leading and controlling activities to ensure optimal performance and success in various organizational contexts. Studying the academic course ‘Management and its need, scope and significance in the modern period’ is very important. This study helps in comprehending the intricacies of organizational structures, processes and behaviors. The study aims to assess the academic course ‘Management’ and its need, scope and significance in the modern period. The study’s design is qualitative and most of the data sources are secondary. This is review based paper. This study offers a comprehensive understanding of organizational dynamics, strategic thinking, resource management and ethical considerations, enabling graduates to contribute effectively to the success of organizations in today’s complex and ever-changing business landscape.